Taxpayers' adoption of online tax return reporting: extended meta-UTAUT model perspective - Asep Heri Hermanto; Nila Armelia Windasari; Mustika Sufiati Purwanegara (Cogent Business & Management, 2022)
This research examines dominant technology adoption paradigms to discover vital underlying variables in online tax return reporting behavior. This research aims to develop and empirically test a hypothetical model based on data collected from Indonesia's existing online tax return reporting users. This research was conducted by distributing an online questionnaire nationwide and obtaining 486 taxpayer data for further analysis. The findings show that trust, effort expectancy, and performance expectancy positively and significantly impact taxpayers' attitudes towards online tax return reporting. Facilitating conditions and attitudes positively and significantly impact the taxpayer intention to adopt online tax return reporting. However, the intention of taxpayers to use online tax return reporting is unaffected by social influence. Taxpayers' behavioral intentions positively and significantly impact their user behavior. At the same time, grievance redressal and anxiety had a significant influence as moderating variables. Implications for practice and research are also discussed.
Keywords: 650; adoption; e-filing; meta-UTAUT; online tax return reporting; use behavior